Representation Uchi and Soto Concept in Japanese Social Deixis - Arfianty, Rani; Mulyadi, Mulyadi (KIRYOKU, 2024)
This study aims to describe the representations of uchi and soto in the textbook Marugoto: Japanese Language and Culture Intermediate 1 B1 recommended by The Japan Foundation using the context and deixis theory approach by (Levinson, 1983; Stassler, 1982). Also, the social deixis of Japanese is explained (Wetzel, 2011). Qualitative descriptive method is used for the presentation of data analysis. The results of this study found that the concepts of uchi and soto in Japanese society are closely related to the social deixis of Japanese. In the analysis it was found that social deixis is also closely related to the use of keigo (expression of respect) as well as the phrase yarimorai (give and take). The close relationship between social deixis and the concepts of uchi and soto illustrates the structural order of Japanese society's life which pays close attention to the position and social status of society when interacting and communicating with each other. By choosing the diction of the words used between the speaker and the interlocutor when communicating, it can be assessed whether both of them belong to the uchi or soto class. The results of this study also at the same time prove the statement of (Wetzel 2011). Marugoto's textbook: Japanese Language and Culture Intermediate 1 B1 presents an explanation of the use and context of how Japanese is actually used by the people by showing the concepts of uchi and soto